Periodontal Disease Behavior in Children and Adolescents with Diabetes in Cienfuegos in 2008 - Arasay Calzada Bandomo; Esther María Castillo Betancourt (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: chronic inflammatory periodontal diseases are a set of entities of multifactorial etiology. Diabetes mellitus is one of the conditions with a great impact on the periodontium and its interaction with microorganisms. Objective: to characterize the behaviour of periodontal disease in children and adolescents with diabetes in Cienfuegos in 2008. Method: an epidemiological, descriptive and cross-sectional study was conducted. The sample included diabetic children and adolescents under 19 years old who attended the endocrinology clinic of the Pediatric Teaching Hospital ''Paquito González Cueto" in the province of Cienfuegos, from January to November 2008. The Russell's Periodontal Index and the Simplified Oral Hygiene Index were applied. The following clinical variables were considered: metabolic control, duration of diabetes mellitus and nutritional assessment. A data-collecting form was used for data analysis. For the statistical processing SPSS (15.0) and Chi square statistical tests were used. Results: a highly significant dependence between oral hygiene and the prevalence and severity of periodontal disease was found as well as a strong association between the lack of metabolic decontrol and periodontal disease. Conclusion: there is a high prevalence of periodontal diseases in children and adolescents with diabetes in the province of Cienfuegos.